Food Control System in Libya - Thuraya Ahmed Abuhlega (Indonesian Association of Food Technologists, 2023)
The food control system in the country should be effective and able to ensure the safety and quality of food. The study aimed to assess the current situation of the food control system in Libya. The mandates of food control are fragmented among different bodies, which sometimes perform the same functions and thus cause an unnecessary burden on the country's budget. Although there appear to be activities related to national standards that align with international standards, the 1973 health law has yet to be updated. The food inspection has not been based on a risk analysis. Also, there are inadequate laboratory support services, and laboratories are unaccredited. There is also an absence of action plans in both the short and long term for information, communication, and education. The inspectors need training, especially in risk-based inspections. Importantly, analysts' lack of expertise makes determining the compliance of food products with Libyan legislation difficult. Poor-quality and unsafe foods enter Libya due to the control system's weakness and the political crisis; therefore, the government should implement an integrated food control system to improve the situation. As well, the United Nations should politically support Libya's stability.